Metodologia de avaliação e diagnóstico da gestão hospitalar com base no Programa Gaúcho de Qualidade e Produtividade e no Programa de Acreditação Hospitalar - Portela, Odete Teresinha (2006)
Currently, hospital organizations represent the most wmplex contemporary companies due to their structure, processes and ciients specificities. In order to achieve the hospital aims, its management should be concemed with business as well as health assistance, improving the scarce financia1 resources to offer qualified assistance to the population. In this area, it is increasing the difficulty to access speciaiiied services, mainly regarding poorer communities. Perhaps, it is because of the govemment lack of intemt and low investtnents in public policies and preventive health care, thereby aggravating the problems faced by these organizations management. In this health chaos, it is necessary to invest in the hospital management system, either public or private. Therefore, the objective of this research is to propose an evaluation and diagnosis methodology of hospital management based on the Productivity and Quality Gaucho Pmgram (PQGP) and the Brazilian Program of Hospital Accreditation. This study is a descriptive, qualitative and bibliographical research that made it possible to develop a comparison between the two programs critena in order to verifi convergent and divergent aspects. After this analysis it was found that both programs present compatible and complementary aiteria. Thus, the evaluation methodology proposed will benefit assessment and diagnosis of health institutions, satisfying specific criteria, including legislation, and will enable the organization to score points and to get prizes offered by the PQGP as a reward for the effort to the improvement of the sewices quality and aiming at excellence.